Multiple Pseudomonas species secrete exolysin‐like toxins and provoke Caspase‐1‐dependent macrophage death. (26th July 2017) - Basso, Pauline; Wallet, Pierre; Elsen, Sylvie; Soleilhac, Emmanuelle; Henry, Thomas; Faudry, Eric; Attrée, Ina
Summary: Pathogenic bacteria secrete protein toxins that provoke apoptosis or necrosis of eukaryotic cells. Here, we developed a live‐imaging method, based on incorporation of a DNA‐intercalating dye into membrane‐damaged host cells, to study the kinetics of primary bone marrow‐derived macrophages (BMDMs) mortality induced by opportunistic pathogen Pseudomonas aeruginosa expressing either Type III Secretion System (T3SS) toxins or the pore‐forming toxin, Exolysin (ExlA). We found that ExlA promotes the activation of Caspase‐1 and maturation of interleukin‐1β. BMDMs deficient for Caspase‐1 and Caspase‐11 were resistant to ExlA‐induced death. Furthermore, by using KO BMDMs, we determined that the upstream NLRP3/ASC complex leads to the Caspase‐1 activation. We also demonstrated that Pseudomonas putida and Pseudomonas protegens and the Drosophila pathogen Pseudomonas entomophila, which naturally express ExlA‐like toxins, are cytotoxic toward macrophages and provoke the same type of pro‐inflammatory death as does ExlA + P. aeruginosa . These results demonstrate that ExlA‐like toxins of two‐partner secretion systems from diverse Pseudomonas species activate the NLRP3 inflammasome and provoke inflammatory pyroptotic death of macrophages.